Bystander-witnessed cardiac arrest is associated with reported agonal breathing and leads to less frequent bystander CPR. (June 2018) - Brinkrolf, P.; Metelmann, B.; Scharte, C.; Zarbock, A.; Hahnenkamp, K.; Bohn, A.
Abstract: Aim: Although the importance of bystander cardiopulmonary resuscitation has been shown in multiple studies, the rate of bystander cardiopulmonary resuscitation is still relatively low in many countries. Little is known on bystanders' perceptions influencing the decision to start cardiopulmonary resuscitation. Our study aims to determine such factors. Materials and methods: Semi-structured telephone interviews with bystanders of out-of-hospital cardiac arrests between December 2014 and April 2016 were performed in a prospective manner. This single-center survey was conducted in the city of Münster, Germany. The bystander's sex and age, the perception of the victim's breathing and initial condition were correlated with the share of bystander cardiopulmonary resuscitation in the corresponding group. Results: 101 telephone interviews were performed with 57 male and 44 female participants showing a mean age of 52.7 (SD ± 16.3). In case of apnoea 38 out of 46 bystanders (82.6%) started cardiopulmonary resuscitation; while in case of descriptions indicating agonal breathing 19 out of 35 bystanders (54.3%) started cardiopulmonary resuscitation (p = .007). If the patient was found unconscious 47 out of 63 bystanders (74.7%) performed cardiopulmonary resuscitation, while in cases of witnessed cardiac arrest 19 out of 38 bystanders (50%) attempted cardiopulmonary resuscitation (p = .012). Witnessed change of consciousness is an independent factor significantly lowering the probability of starting cardiopulmonary resuscitation (regression coefficient −1.489, p < .05). Conclusion: The witnessed loss of consciousness was independently associated with a significant reduction in the likelihood that bystander-CPR was started. These data reinforce the importance of teaching the recognition of early cardiac arrest.